ANALISIS IMPLEMENTASI ISAK 120 TERHADAP KINERJA KEUANGAN (STUDI KASUS : PERUSAHAAN TAMBANG TERBUKA PT BTA) - Gibran, Bramantyo Elvioza (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to analyse the implementation of ISAK 120 on the financial performance of open-pit mining company PT BTA. ISAK 120, effective from January 1, 2024, regulates the recognition, initial measurement, and subsequent measurement of stripping activity assets during the production phase in open-pit mining. This research uses a case study approach by collecting data through observation, interviews, and documentation during an internship at PT BTA. The results show that, up to the time of the research, PT BTA had not implemented ISAK 120 in its open-pit mining activities. Simulation of ISAK 120 implementation indicates potential improvement in financial performance through capitalization of stripping costs as assets, thus providing a fairer view of the company’s financial position. This study recommends that PT BTA consider adopting ISAK 120 to enhance the transparency and relevance of financial statements in accordance with applicable accounting standards. Keywords: ISAK 12O, Financial Performance, Stripping Activities, Open-Pit Mining Company, Cost Capitalization